Nonlinear System Identification using Uncoupled State Multi-model Approach: Application to the PCB Soldering System - Khouni, S.; Hemsas, K. E. (Engineering, Technology & Applied Science Research, 2020)
Multi-model approach is an adapted tool of modeling nonlinear systems. The underlying idea is to simplify the complex nature of the system to be studied by decomposing it into simple (linear) sub-systems, in order to simplify the study (stability, control law, surveillance, etc.). This technique allows us to extend the application of linear systems methodology to nonlinear systems. This paper presents nonlinear system identification using an uncoupled state multi-model applied to a Printed Circuit Boards (PCB) soldering system. Precision, simplicity, and fidelity of the obtained results show the effectiveness of the used algorithm to identify, model, and write down as simple sub-systems, a complex black box system.